Three-point bending behavior and microstructural evolution of ZM20E, ZM20EX and AZ31 tubes - Hu, Ke; Le, Qichi; Zhou, Weiyang; Li, Chunyu; Liao, Qiyu; Yu, Fuxiao (Materials characterization, 2020)
Aimed at optimizing and stabilizing the mechanical performance in collapse mode of cylindrical tubes for wrought magnesium alloys, a comparative experiment is designed to investigate the mechanical responds and microstructural evolution of three kinds of magnesium alloy tubes in three-point bending test under different indenter velocities (1, 10, 60, 240 mm/min). The tested alloys are AZ31, Mg-Zn-Mn-Ce and Mg-Zn-Mn-Ce-Ca alloys, respectively. The EBSD analysis shows bending behavior is closely related with the deformation mechanism such as basal slip or twins. The results show the initial microstructure and texture have significant influence on bending behaviors. The as-extruded Mg-Zn-Mn-Ce tubes present 〈02-21〉//ED texture component, which has nearly equal Schmidt Factor for basal slip and tension twins, inducing excellent ductility with the maximum elongation of 40%. No obvious cracks is found on the top surface of Mg-Zn-Mn-Ce tubes after bending, indicating the whole tube subject tensile strain during bending process. It leads the high energy absorption capacity, nearly 1.4 times of that of AZ31 alloys at low strain rate. 〈51-63〉//ED and 〈01-11〉//ED texture components in Mg-Zn-Mn-Ce-Ca tubes induce the basal slip dominated deformation mechanism, leading the stable energy absorption capacity. The strong fiber texture and relatively coarsened microstructure of AZ31 tubes lead the relatively high peak load, but low energy absorption capacity. •The energy absorption capacity of magnesium alloy pipe is closely related to its plasticity.•basal slip deformation mode stabilizes the tube's energy absorption capacity.•The mechanical performance of three point bending is closely related to the alloy’s initial texture and grain structure.